Best Practices and their Influence on Decision Making: A Comprehensive Systematic Review. - Astete-Llerena, J. (2025)
The use of best decision-making practices is having a positive impact in various environments such as business, government, and education. By following these practices, organizations make better decisions, achieve their objectives more effectively, and improve the quality of their work. The primary objective of this study is to determine the state of the art of research on the impact of best practices for decision-making over the past 7 years. An exhaustive literature study was conducted using various documentary sources such as Scopus, Web of Science, Science Direct, ARDI, EBSCOhost, and ProQuest. These sources were used to develop search strategies, which allowed finding a total of 8658 relevant studies. To refine the results, exclusion filters based on the PRISMA Diagram model were applied. As a result of this process, 63 high-quality papers were finally selected for a systematic review. The results of the SRL indicate that China, Switzerland, and the United States are the most productive countries in the analyzed research, with a greater presence of productivity in the European continent. Likewise, Sustainability and Value and Health are the most frequently appearing scientific journals in the research. This study presents significant findings where these selected papers provide relevant context to the study topic.